Zakat, Infak, dan Sedekah: Modal dan Model Ideal Pembangunan Ekonomi dan Keuangan Modern - Suma, Muhammad Amin (Faculty of Shariah and Law, 2013)
Zakat is designation for a particular property that intentionally released to be channeled to mustahiq. Other financial types that always accompanies or included with it are zakah, infak, and sedekah (ZIS). ZIS funds can be considered as a triad of economic resources and short-term Islamic finance in synergy with other funding sources, such as grant, wills, and endowments-oriented for long-term interest. In addition to its management structure and mechanism is relatively simple and efficient, zakah can be said always completely ready to cope with urgent needs. ZIS funds in enforceability of all peoples and Muslim nations showed that zakah system appropriate to be used as capital and financial economic model and the most modern of all time.DOI: 10.15408/aiq.v5i2.2121